Psychological Status and Related Factors in Medical Isolated Persons during Outbreak of COVID-19 - Qin WANG; LI Li; Xia ZHOU; Zhimei LIU; Bingshan GUO; Renqi DONG (康复学报)
Objective:To evaluate the mental health status of the residents in the epidemic area of Corona Virus Disease 2019 (COVID-19) and analyze its influencing factors, so as to provide evidence for psychological intervention timely for the quarantine population in special period.Methods:A total of 130 residents in COVID-19 epidemic area of Jinan were collected with general data and their anxiety/depression state was assessed through an online questionnaire from February 9th to 11th,2020. The General Anxiety Disorder Scale-7 (GAD-7) was used to evaluate anxiety state, and the Patient Health Questionnaire-9 (PHQ-9) depression screening scale was used to evaluate depression state.Results:1) Among the 124 medical isolation residents,106 (85.48%) had anxiety-related mood changes (GAD-7>4) and 96 (77.42%) had depression-related mood changes (PHQ-9>4).2) Univariate analysis showed that the educational level, the scores of GAD-7 were statistically significant with different educational levels, the amount of negative information received about the COVID-19 and occupational classification (P=0.03, P=0.002, P=0.04), while the scores of PHQ-9 were statistically significant with different marital status, educational levels, occupational classification (P=0.04, P=0.002, P=0.02).3) Multiple Logistic regression analysis showed that the amount of negative information received about the COVID-19 (OR=2.855, P<0.001) was a risk factor for anxiety among medical isolated persons during the epidemic, while there was a protective factor in educational level (OR=0.656, P=0.175). The marital status (OR=0.211, P=0.008) and the educational level (OR=0.518, P=0.039) were protective factors for depression among medical isolated persons, and there was a protective factor trend in educational level. Health care workers, students and freelancers showed different trends in their role compared with the employed persons. Health care workers and freelancers were the statistically significant risk factors for anxiety in medical isolated persons individuals (OR=6.633, P=0.028; OR=2.404, P=0.027), while health care workers were the statistically significant risk factors for depression in medical isolated persons (OR=5.966, P=0.030).Conclusion:During the epidemic period of COVID-19, the psychological and emotional changes in the medical isolated persons were significant. The main influencing factors were the amount of negative information received from the COVID-19 and the marital status. Negative information overload is a risk factor for anxiety in isolated people, and marriage is a protective factor for depression. Educational level is the protective factor for depression and tends to protect risidents from anxiety. Different occupation has influence on the occurrence of anxiety and depression, and medical profession is a high-risk group.